Estudio sobre el teletrabajo en los colegios privados en el distrito de La Molina para generar ventajas competitivas a nivel primario - Torre Polo, Aaron David (2022)
This project arises with the objective of identifying the competitive advantages generated by the modernization of teaching methodologies at the elementary level. This phenomenon occurs thanks to the development of new technologies which facilitate the use of new resources for education. As a result of the global situation, we are going through, teachers and educational institutions have been forced to develop a new remote work scheme, better known as teleworking. This element is already a new normal today in different industries. And in the education sector, numerous educational institutions have been going through a transition process from face-to-face to virtual education. Although it is not yet fully approved by all group of parents in Peru, there are success stories in different parts of the world where it is shown that this new teaching method provides competitive advantages to educational institutions, as it improves the learning process, it makes it more dynamic and enriches the educational material. In addition, it involves the student even more in his learning process; also, it allows him to enjoy the flexibility and practicality of this method, shortening distances that were impossible to reach in person.